The Motivation to Participate in Physical Activity and Its Impact on Academic Performance in Public Higher Learning Institution - Mohamad Hsbollah, Hafizah; Hassan, Haslinda; Raja Mohd. Ali, Raja Haslinda (International Journal of Psychosocial Rehabilitation, 2019)
This study focuses on examining the motivational factors that influence public university students to participate in physical activity and the impact of such participation on their academic performance. Previous study has revealed that exposure to technology has resulted in reduced participation in physical activity among Malaysian children, preteens and teenagers, and that about nearly half of Malaysian adults were physically inactive. Hence, concerns have arisen that participation in physical activity would continuously decline as these young people become older. At this stage, little is known about the motivation factors that influence the participation of physical activity among Malaysian youth and its impact on the academic performance. Data were collected by distributing a questionnaire to students in a Malaysian public university. Results reveal four motivational factors, namely, enjoyment, mastery, and physical appearance positively affect participation in physical activity. Further, the study found a significant but negative relationship between participation in physical activity and academic performance. Hence, it is suggested that being frequently active in physical activity, at certain point could reduce students’ cumulative grade point average (CGPA). As this study used of a self-reported questionnaire to measure the level of participation in physical activity, further test needs to conducted to confirm such relationship. The findings of this study add to the body of knowledge and can be a useful reference on the motivational factors that influence students’ participation in physical activity and its negative relationship with academic performance. The findings could be also used to design an intervention programme to promote physical activity and suggest solutions for active students to achieve a university-life balance.